(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This study aimed to identify the impact of leadership styles on the organizational performance of Yemeni pharmaceutical companies, with job satisfaction as a mediating variable, the study used the Comparative method of previous studies that dealt with the field of research. The study reached a set of results, the most prominent of which were: the existence of an average level for each of the styles of leadership (transformational, democratic, servant, and participatory), and the existence of an average level of organizational performance and job satisfaction in Yemeni pharmaceutical companies. In the light of the results, the study recommended the need for managers in Yemeni pharmaceutical companies to do everything that would increase, develop and improve the practice of transformational leadership because of the features and characteristics that affect the behavior of leaders and their actions with all parties within the company environment, and focus on involving employees in decision-making. The importance of participatory leadership in increasing employees’ self-confidence, which in turn is reflected in achieving excellence in performance.